A biomechanical assessment of the relation between the oral implant stability at insertion and subjective bone quality assessment - Ghada Alsaadi, Marc Quirynen, (Blackwell Synergy, 2007)
Aim: The study was set to evaluate the validity of subjective jaw bone quality assessment. Materials and Methods: A total of 298 patients (198 females, mean age 56.4) were treated with oral implants at the Periodontology Department at the University Hospital of KUL. A total of 761 TiUnitet implants have been installed. Subjective bone quality assessment was performed on radiographs and by the surgeon’s tactile sensation and was compared with torque measurements. In a subset of patients, implant stability was also assessed by implant stability quotient and/or periotest values. Results: Subjective assessment of bone quality was related to the PTV, ISQ and placement torque [in the crestal, the second and the apical third (N cm)], respectively; in grade 1: 5.3, 73.3 (4.2, 9.6, 15.2), and grade 3 or 4: 1.6, 55 (3.3, 5.5, 8.4). For the surgeon’s tactile sensation, a good correlation was noted for the presence of a thick cortex: 4.6, 70.3 (4.2, 9.7, 15.1), or a thin one: 0.3, 65.9 (3.6, 6.9, 10.1). For dense trabecular bone, the values were 2.8, 69.4 (4.4, 9.7,14.8), while for poor trabecular bone, the values were 1.7, 66.4 (3.6, 6.4, 9.8). Conclusions: Subjective assessment of bone quality is related to PTV, ISQ and placement torque measurements at implant insertion.